Diagnosis of Breakthrough Fungal Infections in the Clinical Mycology Laboratory: An ECMM Consensus Statement - Jenks, Jeffrey D. (2021)
ECMM Council Investigators: Z. Adamski, S. Arikan-Akdagli, V. Arsic-Arsenijevic, O.A. Cornely, N. Friberg, N. Gow, S. Hadina, P. Hamal, M. Juerna-Ellam, N. Klimko, L. Klingspor, F. Lamoth, M. Mares, T. Matos, V. Ozenci, T. Papp, E. Roilides, R. Sabino, E. Segal, A.F. Talento, A.M. Tortorano, P. Verweij.